Rifting/spreading propagation interacts with preexisting transform faults: 3D geodynamic modeling - Li, Hao; Liao, Jie; Shen, Yongqiang; Qing, Jiarong; Wu, Yangming; Zhao, Zhongxian; Shi, Xiaobin (Frontiers in Earth Science, 2023)
The divergent rifting/spreading centers and the strike-slip transform faults are the essential tectonic units on Earth, dynamic evolution of which regulates the development of rifting/spreading basins. The propagation of rifting/spreading centers may interact with pre-existing transform faults, but how they interact with each other remains enigmatic. We use three-dimensional geodynamical numeric models to systematically simulate the interaction between rifting/spreading propagation and the pre-existing transform faults. Our model results provide the following findings. (1) The pre-existing transform faults affect rifting/spreading propagation promoting the formation of ridge segments with an offset distance. Yet, the evolution of the transform faults is regulated by rifting/spreading propagation, featured by the increase of its length and the presence of lineated magmatism. (2) The initial length and orientation of the pre-existing transform faults largely affect rifting/spreading propagation, i.e., large transform fault length favors the formation of large offset between ridge segments, and oblique transform faults facilitate the formation of overlapped spreading centers. (3) Model results shed new light on the evolution of the South China Sea, implying that the observed ridge segments in the eastern and southwestern sub-basins and the lineated volcanos along the Zhongnan Transform Fault are the results of the interaction between the rifting/spreading propagation and the pre-existing transform fault.